A novel biodegradable poly(propylene carbonate) with enhanced thermal and mechanical properties by incorporating tannic acid. (15th December 2021) - Yang, Jianing; Zhang, Xuhui; Li, Ting; Wang, Yang; Xia, Bihua; Jiang, Jie; Chen, Mingqing; Dong, Weifu
Abstract: It is a challenge to simultaneously enhance the thermo‐oxidative stability, mechanical properties and biodegradability of biodegradable polymer. In this work, by incorporating tannin acid, a natural compound with polyphenol hydroxyl, a biodegradable poly(propylene carbonate) (PPC) with improved thermo‐oxidative stability and biodegradability was successfully prepared. Besides, due to the existence of plentiful hydrogen bond between PPC and tannic acid (TA), the composite exhibits an obviously improved Young's modulus and yield strength while retaining a high break strain (>350%). The improved comprehensive properties should be ascribed to the abundant polyphenol hydroxyl in TA, which can consume oxygen, enhance the hydrophilia of PPC/TA composites and constructing plentiful hydrogen bond with PPC. We envision that this work offers a facile route to prepare PPC with high thermo‐oxidative stability, mechanical properties, and biodegradability, and will promote the practical use of PPC.